2008
DOI: 10.1080/15567030701438715
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Chars from Bursa Mustafa Kemal Paşa Alpagut and Balıkesir Dursunbey Çakirca Lignite (Turkey) during Non-catalytic and Catalytic Gasification

Abstract: The reactivities of chars obtained by pyrolysis of Bursa Mustafa Kemal Paşa Alpagut lignite and Balıkesir Dursunbey Çakırca lignite (Turkey) at different temperatures were determined by CO 2 gasification and by combustion with O 2 . Catalytic effect of Na 2 CO 3 on the CO 2 and O 2 gasification reactivity of chars was investigated. Gasification tests were performed in the fixed bed reactors operating at ambient pressure. Reactivity of chars during the CO 2 gasification reactions was determined by calculating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Mineral matter content of coals is known to influence gasification reactivity because of the presence of catalytically active components. The potential of catalysis in high‐temperature CO 2 gasification was discussed elsewhere 11. 12 Walker et al 1.…”
Section: Resultsmentioning
confidence: 99%
“…Mineral matter content of coals is known to influence gasification reactivity because of the presence of catalytically active components. The potential of catalysis in high‐temperature CO 2 gasification was discussed elsewhere 11. 12 Walker et al 1.…”
Section: Resultsmentioning
confidence: 99%
“…The potential of catalysis in high-temperature CO 2 gasification was discussed elsewhere. [11,12] Walker et al [1] showed that K and Na added to low-rank coals by ion exchange and high-rank coals by impregnation were excellent catalysts for char gasification in O 2 , CO 2 , and H 2 O. Fernµndez-Morales et al [12] showed that R CO 2 correlated well with the amount of Ca in chars prepared from several lignites. R CO 2 at 900-1200 8C was related to the amount of Fe 2 O 3 , CaO, MgO, Na 2 O, and K 2 O in the chars.…”
Section: Relationship Between Mineral and Reactivitymentioning
confidence: 96%